STUDIES ON BODY WEIGHTS OF ASSAM LOCAL AND ASSAM LOCAL CROSSBRED GOATS - Bula Das; D. Das; A. Aziz; D. Kalita; T. C. Roy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Data on body weights at birth, 1 and 3 months of age each of 246 kids, 6 months of age of 212 and 12 months of age of 152 kids belonging to three genetic groups, maintained at 3 different farms of Assam Agricultural University, covering a period of 10 years (1990-1999) were utilized. The least-squares means (µ) of body weights at birth, 1, 3, 6 and 12 months of age were 1.44 ± 0.02, 3.14 ± 0.06, 5.84 ± 0.10, 9.00 ± 0.15 and 13.85 ± 0.23kg respectively. Genetic group, sex, season and type of birth exerted significant effect on body weights at all the ages, excepting the effect of season on 1 month body weight, kidding order at all the ages and type of birth on birth and 12 months body weight which were found to be non-significant. The results showed an increasing trend of the weight of the kids with the increase in Beetal inheritance. Males were significantly heavier than the females. Singlets were found to be heavier to multiples.